Broken words, furious wasps. How should we translate the sonic materiality of Araweté ritual singing? - Guilherme Orlandini Heurich (Journal de la Société des Américanistes)
In Araweté ritual singing, the performance of oporahẽ songs is an exercise in downplaying referential meaning without the actual removal of the sounds of the language. These songs are performed in a way that effectively break words into syllables, which are recombined to form unusual and “meaningless” words. Phrased differently, a good amount of these songs’ “meaning” is not in the things to which they are referring. By looking at the effect of this displacement of syllables in the performance and in the written rendering of the Araweté’s oporahẽ songs, this paper addresses the role of translation in anthropological practice when referential meaning is not easy to access. Following recent approaches in linguistic anthropology, the paper argues that an attention to the materiality of sound and voice in Araweté ritual singing provides a framework for understanding the performance and translation of songs in indigenous Amazonia.